Intertidal community of fucoid seaweeds in the Yarnyshnaya Bay, the Barents Sea - Kapkov V. I.; Shoshina E. V. (Vestnik MGTU, 2021)
The specific and spatial structure of benthic algal community on the littoral zone in the east area of Murman coast of the Barents Sea (69°11'78''N, 36°04'38''E) has been studied in the conditions of anthropogenic influence absence. As a material for studying indicators of fucoid community and populations of dominating species in connection with habitats own long-term seasonal observations and data of scientific expeditions of 1994–2017 have served. The species composition of littoral phytocenosis consists of 39 species including 18 brown, 9 red and 12 green seaweeds, with prevalence on number of annual and seasonal species, on a biomass – perennials. Ecological factors influence essentially on seaweed distribution in different sites of the littoral zone. The major abiotic factors are presence of firm substratum, surf and storms, ice motion. Seaweed littoral community had multi-level structure, in which the basic layer was occupied by brown seaweeds with numerous litophytes and epiphytes under beds and on thallus of dominant species. The community algal biomass in the littoral zone was from 2.8 ± 0.6 up to 17.7 ± 2.9 kg/m² and depended on the species structure, substratum for benthic seaweeds, surf and tides. The biomass and density of fucoid seaweeds varied over a wide range in different biotopes under a natural rigid press of seasonal changes of environmental factors (temperature, surfs, storms) during tides and under natural damages of littoral community in the arctic region. As a whole littoral fucoid phytocenosis of the bay could be considered as an example of adaptation of seaweeds populations to the conditions of the northern seas. The received results could be useful for estimating ecological status of coastal ecosystem, at stock assessment of commercial seaweeds and for algal aquaculture development in the Barents Sea.